Republic of Croatia : Financial System Stability Assessment; Update. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The 2002 Financial Stability Assessment Program (FSAP) found that the Croatian financial system was resilient, but vulnerabilities remain. The authorities have been proactive in addressing macroeconomic and financial vulnerabilities associated with rapid credit growth and have also taken prudential measures on contingency planning with supervisory authorities of foreign banks coupled with efforts to enhance risk awareness and strengthen home-host coordination. The Croatian National Bank (CNB) has put in place an effective bank supervision framework. The assessment reflected a legal and regulatory framework together with banking supervision practices of the Croatian authorities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet